Management strategies for isolated premature thelarche: a risk-stratified clinical pathway favoring “watchful waiting” - Xu, Yan; Cui, Hongtao; Wang, Xinna; Liu, Fang (Frontiers in Endocrinology, 2026)
Isolated Premature Thelarche (PT) is a common clinical issue in pediatric endocrinology. Because its early presentation resembles that of Central Precocious Puberty (CPP), which requires intervention, its management is highly controversial, caught between “active intervention” and “watchful waiting.” This leads to inconsistent clinical practices and significant anxiety for affected families. This review aims to move beyond this traditional dichotomy by conducting an in-depth analysis of the natural history, pathophysiological mechanisms, diagnostic criteria, and progression risks of PT. We propose a new paradigm for a tiered, individualized management approach based on risk stratification, providing a clear, evidence-based pathway for clinical decision-making. Through a comprehensive review of recent clinical studies, reviews, and expert consensus, this paper analyzes the theoretical basis and evidence supporting a “watchful waiting” strategy. It defines the rigorous initial evaluation and dynamic monitoring protocols required for its implementation and clarifies the quantitative indicators for transitioning from “observation” to “active intervention.” For children with typical PT—characterized by a normal growth rate, no significant bone age advancement, a prepubertal pelvic ultrasound, and a very low basal luteinizing hormone level—”watchful waiting” or “active surveillance” is a safe, effective, and preferred management strategy. This is an active medical monitoring process, not passive waiting. “Active intervention” (i.e., Gonadotropin-Releasing Hormone agonist therapy) should be strictly limited to the few “progressive” cases that show sustained pubertal progression, growth acceleration, and significant bone age advancement during follow-up, and are confirmed as CPP by a Gonadotropin-Releasing Hormone stimulation test. The risk-stratified management pathway proposed herein aims to effectively address the clinical dilemma, avoid over-treatment, and achieve individualized, precise management for children with PT.